Pyrazolo[1, 5-a]pyrimidine TRPC6 antagonists for the treatment of gastric cancer. (28th September 2018) - Ding, Mingmin; Wang, Hongbo; Qu, Chunrong; Xu, Fuchun; Zhu, Yingmin; Lv, Guangyao; Lu, Yungang; Zhou, Qingjun; Zhou, Hui; Zeng, Xiaodong; Zhang, Jingwen; Yan, Chunhong; et al.
Abstract: Transient receptor potential canonical 6 (TRPC6) proteins form receptor-operated Ca 2+ -permeable channels, which have been thought to bring benefit to the treatment of diseases, including cancer. However, selective antagonists for TRPC channels are rare and none of them has been tested against gastric cancer. Compound 14a and analogs were synthesized by chemical elaboration of previously reported TRPC3/6/7 agonist 4o . 14a had very weak agonist activity at TRPC6 expressed in HEK293 cells but exhibited strong inhibition on both 4o -mediated and receptor-operated activation of TRPC6 with an IC50 of about 1 μM. When applied to the culture media, 14a suppressed proliferation of AGS and MKN45 cells with IC50 values of 17.1 ± 0.3 and 18.5 ± 1.0 μM, respectively, and inhibited tube formation and migration of cultured human endothelial cells. This anti-tumor effect on gastric cancer was further verified in xenograft models using nude mice. This study has found a new tool compound which shows excellent therapeutic potential against human gastric cancer most likely through targeting TRPC6 channels. Graphical abstract: Image 1 Highlights: A potent TRPC6 antagonist 14a with the pyrazolopyrimidine skeleton was identified with an IC50 of ∼1 μM. 14a suppressed proliferation of AGS and MKN45 cells as well as gastric tumor growth in a xenograft model for the first time. 14a specifically inhibited TRPC3/6/7 (TRPC6 > C7 > C3) with a very weak effect on TRPC4 and no effect on other TRP channels.